Evaluation of novel xylose-fermenting yeast strains from Brazilian forests for hemicellulosic ethanol production from sugarcane bagasse - Martiniano, Sabrina E. (2013)
Bioconversion of hemicellulosic hydrolysates into ethanol with the desired yields plays a pivotal role for the overall success of biorefineries. This paper aims to evaluate the ethanol production potential of four native strains of Scheffersomyces shehatae (syn. Candida shehatae) viz. S. shehatae BR6-2AI, CG8-8BY, PT1-1BASP and BR6-2AY, isolated from Brazilian forests. These strains were grown in commercial D-xylose-supplemented synthetic medium and sugarcane bagasse hemicellulose hydrolysate. S. shehatae BR6-2AY showed maximum ethanol production [0.48 +/- 0.019 g g(-1), 95 +/- 3.78 % fermentation efficiency (FE)] followed by S. shehatae CG8-8BY (0.47 +/- 0.016 g g(-1), 93 +/- 3.12 % FE), S. shehatae BR6-2AI (0.45 +/- 0.01 g g(-1), 89 +/- 1.71 % FE) and S. shehatae PT1-1BASP (0.44 +/- 0.02 g g(-1), 86 +/- 3.37 % FE) when grown in synthetic medium. During the fermentation of hemicellulose hydrolysates, S. shehatae CG8-8BY and S. shehatae BR6-2AY showed ethanol production (0.30 +/- 0.05 g g(-1), 58 +/- 0.02 % FE) and (0.21 +/- 0.01 g g(-1), 40 +/- 1.93 % FE), respectively.